Tailored laser beam shapes for welding of copper using green laser radiation - Kaufmann, Florian; Roth, Stephan; Schmidt, Michael (International Journal of Advanced Manufacturing Technology, 2024)
The rapid development of laser beam sources and adapted welding technologies in recent years lead to an increased use of laser welding techniques in automated production nowadays. Especially its precision and local energy input are key features for joining applications in electric vehicle components, where joints have to meet both mechanical and electrical requirements as current-carrying connections. However, the copper materials used are difficult to weld due to their physical properties, making a stable process with fewest seam imperfections only feasible within a limited process window. Recently available beam sources emitting visible laser radiation have proven to overcome the low absorptivity at process start, but spattering is still a prone defect significantly affecting process efficiency and quality. Literature approaches for modifying the energy input point to laser beam shaping as a method for reducing process imperfections, which, however, has not been extensively researched in copper processing using green laser radiation. Thus, this study investigates the influence of a shaped intensity profile for visible laser radiation created with a reflective diffractive optical element in laser beam welding with laser powers up to 3 kW. A characterization of the process dynamics is performed by use of high-speed imaging, and metallographic analysis is used to elaborate benefits of the applied beam shapes. With beam shaping, an enlarged heat conduction welding regime and an advantageous seam shape are found. Furthermore, a decrease in spatter formation during deep penetration welding is detected for the elliptical beam profile, which correlates with an oscillation movement of the capillary.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Beam shaping; Copper; Diffractive optical element; Green laser radiation; Laser beam welding; Process observation